Rituximab versus the modified Ponticelli regimen in the treatment of primary membranous nephropathy: a Health Economic Model. Issue 12 (29th March 2018) - Hamilton, Patrick; Kanigicherla, Durga; Venning, Michael; Brenchley, Paul; Meads, David
ABSTRACT: Background: Membranous nephropathy is among the most common causes of nephrotic syndrome worldwide, with a high healthcare burden. Treatment using the modified Ponticelli regimen (mPR) has remained the standard of care for decades, but newer therapies such as rituximab offer promising results with reduced side effects. The cost of this treatment, however, is perceived as a barrier to widespread use, especially in resource limited healthcare systems. Methods: We developed a decision-analytic model to estimate the cost-effectiveness of rituximab versus the mPR from the perspective of the National Health Service in the UK over a 1 year, 5 year and lifetime horizon. Primary outcome is the cost-effectiveness of rituximab versus mPR at 5 years post-treatment. Secondary outcomes are cost-effectiveness at 1 and 10 years post-treatment and over a lifetime. Results: At 1-year post-treatment, rituximab therapy dominates mPR. At 5 years post-treatment, rituximab therapy is cheaper than the Ponticelli regimen but at a loss of 0.014 quality-adjusted life years (QALYs) with an incremental cost-effectiveness ratio (ICER) of £95 494.13. Over a lifetime, rituximab remains the cheaper option with an incremental cost of −£5251.03 but with a reduced quality of life (incremental QALY of −0.512) giving an ICER of £10 246.09. Conclusions: Our analysis indicates that rituximab has the potential to be a cost-effective treatment in the short and medium terms despite the high single-dose cost. This evaluation suggests that further research is warranted and highlights the need for a high-quality clinical trial to confirm the efficacy and cost-effectiveness of rituximab versus the current standard of care.